DERADIKALISASI PEMAHAMAN AJARAN ISLAM - Karwadi Karwadi (AL-TAHRIR, 2014)
We have nowadays witnessed a growing trend of the rising of radical religious thoughts amongst Muslims. They are fanatical people who claim to have correctly understood Islam more than others. Even they blame others who do not follow their way as unbelievers. How do such radical views rise? And how can such views be de-radicalized?  Radical views initially come out and gradually develop because of exclusive religious outlooks. Since outward attitudes reflect one’s deep mind and worldview, one best way to soften radicalism should begin from de-radicalization of one’s ideology and way of thinking. There should be transformation of Islamic religious thoughts from particularistic to rational-imperative, from exclusive to inclusive, from formalistic to perennial, from mono-cultural to multicultural. De-radicalization needs participation from the government, people and academia. Furthermore, de-radicalization must be a context-based effort, paying great attention to socio-historical contexts where this effort is formulated to avoid rising another form of radicalism.Keywords: de-radicalization, exclusive, perennial, multiculturalism